Pancheshwar Multipurpose Project: Nepal’s Portion of Power - Pun, Sant Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
After the proverbial 13 year 'ban bas', the 1996 Mahakali treaty was "re-activated" in 2009 when Nepal and India constituted the Pancheshwar Development Authority to fnalize the Detailed Project Report of Pancheshwar Multipurpose Proj-ect and thereafter undertake the execution, operation and maintenance of the project. In this context, the article reverts back to the ratifcation time of the Mahakali treaty in 1996 and dwells exclusively on the issues then raised pertaining to Nepal’s portion of power from Pancheshwar project. The then prime minister and water resources minister gave CPN-UML party gen-eral secretary and the CPN-UML Mahakali study team coordinator written replies (a) on India being "forced to buy" Nepal's portion of power, (b) that "relevant alternatives" meant "thermal and gas plants and excludes hydropower plants", and iii) that "savings in cost to the benefciaries as compared with the relevant alternatives" meant the same as "avoided cost of alterna-tive principle." No attempts were made to elicit the Government of India's interpretations on these vital issues. Instead, while the water resources minister claimed Rs 21 billion annually from the sale of Nepal's portion of Pancheshwar power to India, the not-to-be outwitted party secretary claimed an astronomical annual revenue of Rs 120 billion. The now incumbent prime minister has come up with another attractive fgure of Rs 45.88 billion annually. The article attempts to point out that if due diligence is not undertaken immediately on the ambiguities prevailing in the Mahakali treaty and the letters of exchange, then Nepal may well end up as like Paraguay vis-a-vis Brazil on the 14,000 MW Itaipu hydropower project. Key words: Pancheshwar Multipurpose Project; Mahakali treaty; Avoided cost; Power revenues; Nepal DOI: 10.3126/hn.v6i0.4186 Hydro Nepal Vol 6, January 2010 Page :1-6 Uploaded Date: 23 January, 2011